2019
DOI: 10.1186/s13722-019-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with willingness to wear an electronic overdose detection device

Abstract: Background North America is in the midst of an opioid overdose epidemic. Although take-home naloxone and other measures have been an effective strategy to reduce overdoses, many events are unwitnessed and mortality remains high amongst those using drugs alone. While wearable devices that can detect and alert others of an overdose are being developed, willingness of people who use drugs to wear such a device has not been described. Methods Drug using persons enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 22 publications
0
39
1
Order By: Relevance
“…While stand-alone studies of willingness to use a biosensor or mobile application-based bystander network have been pursued, there is a lack of data to understand user perception and need for naloxone options that do not require bystander intervention [15,25]. In this study, we investigated the preferences of individuals who use opioids regarding a wearable device capable of detecting and reversing overdose without bystander intervention.…”
Section: Introductionmentioning
confidence: 99%
“…While stand-alone studies of willingness to use a biosensor or mobile application-based bystander network have been pursued, there is a lack of data to understand user perception and need for naloxone options that do not require bystander intervention [15,25]. In this study, we investigated the preferences of individuals who use opioids regarding a wearable device capable of detecting and reversing overdose without bystander intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, this nding was inconsistent with a previous quantitative study that indicated that homelessness was negatively associated with willingness to wear a device to detect opioid overdose and alert bystanders. 21 We suspect the discrepancy may relate to our observation that some participants were distrustful of bystanders who may take advantage of their unconscious state during overdose, and thus preferred a closed-loop system. Populations experiencing homelessness and other high-need populations represent logical rst bene ciaries of future distribution strategies.…”
Section: Discussionmentioning
confidence: 94%
“…A patient preference study conducted in Vancouver found that among the 1,061 adults who use illicit drugs surveyed, 576 (54.1%) said they were willing to wear an overdose detection device. 6 The study found that factors that were positively associated with willingness were previous overdose, current methadone treatment, female gender, and history of chronic pain. 6 Understanding factors that impact the acceptability of wearable overdose detection devices for people who use opioids could help to ensure the uptake of these devices.…”
Section: Issues To Considermentioning
confidence: 96%
“…6 The study found that factors that were positively associated with willingness were previous overdose, current methadone treatment, female gender, and history of chronic pain. 6 Understanding factors that impact the acceptability of wearable overdose detection devices for people who use opioids could help to ensure the uptake of these devices. Devices that are small and can be worn under clothing or that look similar to other commonly worn devices could help to limit the stigma that may be associated with wearing overdose detection devices.…”
Section: Issues To Considermentioning
confidence: 96%